1989
DOI: 10.1037/0735-7036.103.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Presence of female cowbirds (Molothrus ater ater) affects vocal imitation and improvisation in males.

Abstract: In this article we report that imitation and improvisation of tutor songs by eastern male cowbirds (Molothrus ater ater) differs when they are housed with conspecific females as opposed to nonconspecifics. When males, tutored with 12 different song types, were individually housed with females, they developed repertoires composed primarily of improvised and original song types, whereas the repertoires of males housed with canaries were composed entirely of copies of the tutor songs. Song preferences of the fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 18 publications
(41 reference statements)
2
16
0
Order By: Relevance
“…As another example, the Brown-headed cowbird ( Molothrus ater ) is a brood parasitic species (that lays its eggs in the nests of other species, which then raise its hatchlings as their own) that has long been thought to have innate capacities of species-recognition and species-typical song production. (e.g., West and King 1985, 1988; King & West, 1983, 1989) have, however, elaborated the non-obvious influence on male song repertoire of subtle movements made by female cowbirds—movements hardly visible to the unaided human eye—that have the effect of shaping juvenile male song production. The deliberate study of such non-obvious factors, often driven by the dogged investigation of otherwise unusual or unexpected results, has shown that much of what has traditionally been categorized as simply genetic or innate turns out, on closer examination, to be the product of normally occurring experience within a normally occurring, species-typical developmental system or rearing environment (cf.…”
Section: Overview Of Developmental-psychobiological Systems Theorymentioning
confidence: 99%
“…As another example, the Brown-headed cowbird ( Molothrus ater ) is a brood parasitic species (that lays its eggs in the nests of other species, which then raise its hatchlings as their own) that has long been thought to have innate capacities of species-recognition and species-typical song production. (e.g., West and King 1985, 1988; King & West, 1983, 1989) have, however, elaborated the non-obvious influence on male song repertoire of subtle movements made by female cowbirds—movements hardly visible to the unaided human eye—that have the effect of shaping juvenile male song production. The deliberate study of such non-obvious factors, often driven by the dogged investigation of otherwise unusual or unexpected results, has shown that much of what has traditionally been categorized as simply genetic or innate turns out, on closer examination, to be the product of normally occurring experience within a normally occurring, species-typical developmental system or rearing environment (cf.…”
Section: Overview Of Developmental-psychobiological Systems Theorymentioning
confidence: 99%
“…King and West used diacepts to describe populational differences in females' preferences and selectivities for males' songs in cowbirds. During 2 decades of study with this species, researchers have found that the development of male song is influenced by the social environment (King, Freeberg, & West, 1996;West & King, 1996a, 1996bWest, King, & Freeberg, 1997;West, King, & Harrocks, 1983) and that females from different populations can shape male song development on the basis of their populational preferences (King & West, 1989;Smith, King, & West, 2000;West & King, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…We were able to segregate the effects of social and acoustic stimulation in the male's environment by studying the nature of vocal development in naive males housed with female cowbirds, which cannot sing. The studies show that although females cannot serve as fellow performers or models, they can serve as social critics and co-composers West & King, 1985;King & West, 1989).…”
Section: Ontogenetic Outcomes: When Innate Is Not Enoughmentioning
confidence: 99%